Considerations on identification of damage parameters: A case study - Vaz M.* (2015)
The steady growth of commercial codes in recent years has fostered applications of phenomenological approaches to plasticity modelling in industrial settings. Furthermore, metal forming operations involving large plastic deformations are subject to mechanical degradation thereby recommending use of damage models to failure predict. The present work is inserted within this framework in which identification of material parameters for a Gurson-type is discussed for a low alloy carbon steel.